First record of the narrow stink Bug Mecidea lindbergi Wagner, 1954 (Hemiptera: Heteroptera: Pentatomidae: Mecideini) from Turkey - Özgen, Inanç; Çerçi, Bariş (Union of Scientists in Bulgaria - Plovdiv, 2018)
In this study, genus Mecidea is recorded from Turkey for the first time with the species Mecidea lindbergi Wagner, 1954. The newly recorded species is compared with the similar species of the genus Mecidea distributed in the Middle East. © Ecologia Balkanica.
Keywords: Heteroptera; Mecidea lindbergi; New record; Pentatomidae; Turkey